Assessment of phenotypic variability, its heritable components and character association in pomegranate (Punica granatum) genotypes - SINGH, DINESH; SHARMA, NIRMAL; KUMAR, K (The Indian Journal of Agricultural Sciences, 2010)
A study was conducted during 2007 and 2008 among 16 pomegranate (Punica granatum L.) genotypes to estimate the genetic variability in respect of various quantitative and qualitative traits and their association with each other. Wide range of phenotypic variability and genotypic variability was observed in almost all the tree and fruit characters, particularly plant height, plant spread, plant volume, fruit weight, aril size, aril content, TSS, acidity, sugar content and yield/plant. High variability exists for fruit yield-contributing traits, offering opportunity for improvement through selection. Individual plant selection for yield, aril percentage, fruit weight, number of arils and aril : rind ratio would be satisfactorily effective in pomegranate as these characters exhibited high heritability as well as high genetic advance.